THE EFFECTIVENESS TEST OF INFUSION CELERY ROOT (Apium graveolens L.) AS A DIURETIC IN WISTAR MALE WHITE RATS (Rattus Norvegicus): A LITERATURE STUDY - Ida Ayu Dhea Rahnia; Made Krisna Adi Jaya (Journal Pharmaceutical Science and Application, 2022)
Background: Hypertension is defined by persistently elevated arterial blood pressure. The increase in systolic blood pressure is generally>140mmHg or diastolic blood pressure> 90mmHg. The prevalence of hypertension increases with lifestyle changes. Objective: To determine the diuretic effect of celery (Apium graveolens L.) on male wistar rats (Rattus norvegicus). Methods: This research uses a literature study method, the type of the research is descriptive qualitative with literature research (library research) systematic. Results: Based on research data, there were 5 groups of mice that received different treatments. Among the five treatment groups, 0.5 % CMC suspension (KP-) showed the least mean cumulative urine volume, and furosemide suspension (KP+) showed a large mean cumulative urine volume when compared to negative controls. Conclusion: Celery root infusion can increase urine volume, because it contains flavonoids that play a role in increasing urine volume (diuresis). Keywords: Diuretic; Celery (Apium graveolens L.); Furosemide; Hypertension; Wistar rats